2008
DOI: 10.1016/j.nut.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxidized low-density lipoproteins are associated with overweight, obesity, and low serum carotenoids in older community-dwelling women

Abstract: Objective-The objective of this study was to determine whether total serum carotenoids, alphatocopherol, selenium, and obesity were independently associated with oxidized low-density lipoproteins (ox-LDL) in moderately to severe disabled older women living in the community.Methods-Serum ox-LDL, carotenoids, alpha-tocopherol, and selenium were measured in a population-based sample of 543 moderately to severely disabled women, aged 65 and older, in the Women's Health and Aging Study I in Baltimore, Maryland.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
(66 reference statements)
1
9
0
2
Order By: Relevance
“…In particular, it is worth of note that the values of β‐carotene in plasma and LDL were significantly lower in obese subjects than in controls. This is in agreement with previous findings demonstrating a tight association among circulating oxLDL, obesity and serum carotenoids [37], as well as lower levels of antioxidant vitamins in obese subjects than in normal‐weight people [38]. Notably, the finding that α‐tocopherol did not show significant differences between controls and obese insulin‐resistant subjects further support the concept that LDL oxidation is mostly dependent on β‐carotene content in plasma and LDL rather than on vitamin E level [39].…”
Section: Discussionsupporting
confidence: 94%
“…In particular, it is worth of note that the values of β‐carotene in plasma and LDL were significantly lower in obese subjects than in controls. This is in agreement with previous findings demonstrating a tight association among circulating oxLDL, obesity and serum carotenoids [37], as well as lower levels of antioxidant vitamins in obese subjects than in normal‐weight people [38]. Notably, the finding that α‐tocopherol did not show significant differences between controls and obese insulin‐resistant subjects further support the concept that LDL oxidation is mostly dependent on β‐carotene content in plasma and LDL rather than on vitamin E level [39].…”
Section: Discussionsupporting
confidence: 94%
“…Obesity is widely considered to be a strong risk factor for type 2 diabetes and its cardiovascular complications and is an independent risk factor for cardiovascular disease itself 30. Overweight and obesity are associated with higher lipoprotein oxidation, both abdominal and general obesity were shown to be independently associated with circulating oxLDL, weight reduction may potentially reduce oxLDL,31 especially in patients with metabolic syndrome 32. Previous studies have suggested a correlation between anti-oxLDL autoantibodies and anthropometric variables, making anti-oxLDL concentration a potential biochemical indicator of risk of metabolic syndrome 33.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, given the characteristics of the sample, it is possible that the observed inverse association of serum b-carotene with AL was heavily influenced by its known strong association with obesity (38,42) and CRP (39,43) . Previous studies suggest that the inflammatory environment (58)(59)(60)70,71) and obesity-linked oxidation of the lipoprotein carriers of b-carotene, specifically LDL (72,73) , may be related to low serum b-carotene levels.…”
Section: Discussionmentioning
confidence: 99%